A binding site for transcription factor E2F is a target for trans activation of murine thymidine kinase by polyomavirus large T antigen and plays an important role in growth regulation of the gene. - Ogris, E (1993)
The promoter of the murine thymidine kinase gene contains a binding site for transcription factor E2F. Using cell lines (3T3-LT) conditionally expressing polyomavirus large T antigen from a hormone-responsive promoter and reporter gene constructs carrying the thymidine kinase promoter with intact or mutated E2F sites, we show that this E2F site is the target for trans activation by the viral protein. Transcription of the growth-regulated endogenous thymidine kinase gene can be activated in serum-starved, quiescent 3T3-LT cells by induction of T antigen. Activation of transcription from the thymidine kinase promoter requires an intact binding site for the retinoblastoma protein in the T antigen. The same promoter region was furthermore shown to play a major role in growth regulation of the gene. As several other DNA synthesis enzymes also carry E2F binding sites in their promoters, our observations suggest a common mechanism of growth regulation of these genes and that they all might be targets for trans activation by DNA tumor virus proteins.